Practical software model checking via dynamic interface reduction - Guo, Huayang; Wu, Ming; Zhou, Lidong; Hu, Gang; Yang, Junfeng; Zhang, Lintao (Symposium on Operating Systems Principles (SOSP), 2011)
Implementation-level software model checking explores the state space of a system implementation directly to find potential software defects without requiring any specification or modeling. Despite early successes, the effectiveness of this approach remains severely constrained due to poor scalability caused by state-space explosion. DEMETER makes software model checking more practical with the following contributions: (i) proposing dynamic interface reduction, a new state-space reduction technique, (ii) introducing a framework that enables dynamic interface reduction in an existing model checker with a reasonable amount of effort, and (iii) providing the framework with a distributed runtime engine that supports parallel distributed model checking. We have integrated DEMETER into two existing model checkers, MACEMC and MODIST, each involving changes of around 1,000 lines of code. Compared to the original MACEMC and MODIST model checkers, our experiments have shown state-space reduction from a factor of five to up to five orders of magnitude in representative distributed applications such as PAXOS, Berkeley DB, CHORD, and PASTRY. As a result, when applied to a deployed PAXOS implementation, which has been running in production data centers for years to manage tens of thousands of machines, DEMETER manages to explore completely a logically meaningful state space that covers both phases of the PAXOS protocol, offering higher assurance of software reliability that was not possible before.